Waking experience affects sleep need in Drosophila. - Ganguly-Fitzgerald, I; Donlea, J; Shaw, P (2006)
Sleep is a vital, evolutionarily conserved phenomenon, whose function is unclear. Although mounting evidence supports a role for sleep in the consolidation of memories, until now, a molecular connection between sleep, plasticity, and memory formation has been difficult to demonstrate. We establish Drosophila as a model to investigate this relation and demonstrate that the intensity and/or complexity of prior social experience stably modifies sleep need and architecture. Furthermore, this experience-dependent plasticity in sleep need is subserved by the dopaminergic and adenosine 3',5'-monophosphate signaling pathways and a particular subset of 17 long-term memory genes.